The Role of Violence in Graham Greene's The Quiet American (مجلة ديالى للبحوث الانسانية, 2025)
In The Quiet American, the theme of violence is regarded as a major one in the novel. Generally speaking, violence is the state in which specific group of people is exposed to rough unwarranted force. This paper reflects the violence that the Vietnamese witnessed in their daily life during the 20th century by the interferences of other powerful cultures as the American's. It also shows that violence is related to the process of hegemony on the other cultures. In addition, It examines the effects of such hegemony as well as the violence that the Vietnamese culture witnessed.